Agroinoculation: a method of screening germplasm resistance to mungbean yellow mosaic geminivirus - A. VARMA, KAJAL KUMAR BISWAS* and (Indian Phytopathology, 2002)
Agroinoculation of dimeric constructs of cloned DNA-A and DNA-B of an isolate of mungbean yellow mosaic virus (MYMV-Bg) to different varieties of six grain legumes, blackgram (Vigna mungo), cowpea (V. unguiculata), Frenchbean (Phaseolus vulgaris), mungbean (V. radiata), pigeon pea (Cajanus cajan) and soybean (Glycine max) was tested. Two methods of agroinoculation i.e., sprouted seed and seedling inoculation were used and both were found equally effective. Agroinfected plants took longer time to develop symptoms as compared to those inoculated by whitefly (Bemisia tabaci) transmitted plants. Symptomatic and symptomless infection of plants was confirmed by nucleic acid spot (NASH) and Southern hybridization. Some symptomless plants showed positive signal by NASH test but not by Southern hybridization. Contrasting results were, however, obtained for some varieties which could be infected by whitefly inoculation, but not by the agroinoculation. Agroinoculation can be a useful tool for screening for resistance in the breeding programme